The role of technology in community economic empowerment: opportunities and challenges - Willya Achmad (SEAN Institute, 2024)
This research aims to explore the role of technology in community empowerment efforts, with a focus on the opportunities and challenges that arise for MSME actors in its implementation. This research uses a qualitative approach with descriptive methods. The research results show that economic empowerment through the application of technology provides significant opportunities for Micro, Small and Medium Enterprises (MSMEs). Access to information and education via the internet increases the democratization of knowledge, while alternative financing through crowdfunding and peer-to-peer lending expands access to capital. Marketing and sales supported by digital technology enable MSMEs to reach global markets at affordable costs. Operational efficiency through automation and artificial intelligence has a positive impact on productivity. Nonetheless, the digital divide, skills shortages, security and privacy challenges, potential unemployment, and infrastructure and regulatory barriers demand serious attention to ensure the use of technology provides equitable and sustainable benefits.